(untitled) (American Journal of Islam and Society, 2025)
This study investigates the complex interplay between religiosity and sustainable behavior within the broader context of global sustainability, with a particular focus on income as a moderating factor. Utilizing a comprehensive dataset encompassing 46 countries and 53,000 respondents, we introduce income as a crucial socio-demographic variable, thereby illuminating an unexplored facet of this multifaceted relationship. Our methodological approach employs Pooled OLS regression with robust standard errors to address the central research question. The empirical findings reveal a nuanced relationship: while religiosity in isolation appears to exert a negative influence on sustainable behaviors, its interaction with income paradoxically enhances pro-sustainability tendencies. This study posits that the achievement of sustainability is contingent upon the intricate interplay of personal beliefs, societal norms, environmental attitudes, and economic factors. Our research contributes to the existing literature by elucidating the moderating role of income in the religiosity-sustainability nexus. The findings underscore the importance of addressing basic economic needs and integrating religious values in fostering responsible environmental behavior. These insights have significant implications for policymakers and environmental advocates in designing effective strategies to promote sustainable practices across diverse socio-economic and cultural contexts.